Slovak Republic : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that after two years of subdued domestic activity, strong private domestic demand and expansionary fiscal policy in the Slovak Republic buoyed economic growth, which recovered to over 3 percent in 2001. Increased profitability, enterprise restructuring, and reduced corporate income tax boosted fixed investment. Rising real wages and employment, personal income tax reduction, and the redemption of National Property Fund bonds underpinned vigorous growth in private consumption. The general government deficit widened by a half percentage point of GDP to 4 percent of GDP in 2001.